2010
DOI: 10.1002/smll.201000523
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nanocomposite Materials for Cancer Therapy

Abstract: Cancer accounted for 13% of all deaths worldwide in 2005. Although early detection is critical for the successful treatment of many cancers, there are sensitivity limitations associated with current detection methodologies. Furthermore, many traditional anticancer drug treatments exhibit limited efficacy and cause high morbidity. The unique physical properties of nanoscale materials can be utilized to produce novel and effective sensors for cancer diagnosis, agents for tumor imaging, and therapeutics for cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
154
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(154 citation statements)
references
References 188 publications
(217 reference statements)
0
154
0
Order By: Relevance
“…For instance, several solid tumours have defective vasculature and poor lymphatic drainage, due to their rapid growth, resulting in an enhanced permeability and retention (EPR) effect, facilitating the delivery of therapeutics to this region [165,166]. This effect allows nanocarriers to accumulate specifically at the tumour site [167]. Tumour cells are supplied by blood capillaries that perfuse the cells of the tissue, and nanocarriers can passively accumulate or anchor through targeting moieties to biomarkers overexpress by tumour cells.…”
Section: Tissue/tumour Extravasationmentioning
confidence: 99%
“…For instance, several solid tumours have defective vasculature and poor lymphatic drainage, due to their rapid growth, resulting in an enhanced permeability and retention (EPR) effect, facilitating the delivery of therapeutics to this region [165,166]. This effect allows nanocarriers to accumulate specifically at the tumour site [167]. Tumour cells are supplied by blood capillaries that perfuse the cells of the tissue, and nanocarriers can passively accumulate or anchor through targeting moieties to biomarkers overexpress by tumour cells.…”
Section: Tissue/tumour Extravasationmentioning
confidence: 99%
“…Inert metals such as gold and titanium are the ones most commonly used for controlled release of anticancer drugs [154]. Gold NPs (AuNPs) are functional inorganic NPs.…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…Conventional therapy methods in cancer involve the employment of anticancer agents that do not greatly differentiate between cancerous and normal cells (Minelli et al, 2010). Efficient in vivo targeting to heterogeneous population of cancer cells and tissue still requires better selectivity and decreased toxicity to surrounding normal cells, towards a decrease of systemic toxicity, adverse and severe side effects (Liu et al, 2007).…”
Section: Nanotherapymentioning
confidence: 99%
“…Numerous tumors present with defective vasculature and poor lymphatic drainage, due to the rapid growth of solid tumors, resulting in an enhanced permeability and retention effect. This effect allows nanoparticles to accumulate specifically at the tumor site (Minelli et al, 2010;Gil and Parak, 2008). Once the tumor is directly connected to the main blood circulation system, multifunctional Further work in tumor targeting was reported in a subcutaneous model of colon cancer, where it was demonstrated that systemically delivered AuNPs (size, approximately 33 nm) conjugated to tumor necrosis factor (TNF) accumulated in tumors (Paciotti et al, 2004).…”
Section: Tumor Targetingmentioning
confidence: 99%